CLINICAL AND IMMUNOLOGICAL FEATURES OF ATOPIC DERMATITIS IN CHILDREN - Meged E. S.; Yuldashev M. A. (Journals Park Publishing, 2024)
Clinical and immunological features of atopic dermatitis (AtD) were studied in children. IgE-mediated AtD was diagnosed in 76.3% of patients, non-IgE-mediated AtD in 23.7%. A decrease in the relative number of CD3+CD8+ and immunoregulatory index in the peripheral blood was noted in patients with IgE-mediated and non-IgE-mediated AtD. A decrease in the number of CD25+ and an increase in CD16+CD56+ was detected in children with IgE-mediated AtD. In patients with non-IgE-mediated AD, an increase in CD25+ and a decrease in CD16+CD56+ were noted.